(3GdchGcH GdOQGQi aj JQJjH GdeSfO (B( (3eSfO CMeO Hf MfHd(B) (3Ydi CHhGH GdHNGQis - (3CHh GdMSf Ydj Hf MSjf Hf YQhI GdehUdj GdMfHdj,J (B837 (3g` s ((3GHQGgje Hf eMeO Hf eMehO Hf HOQ GdMfHdi s)
(3ChdgG (B:s
(3jHJOF HcJGH GdRcGI s
(3BNQgG (B:s
(3jfJgi HBNQ HGH (B( (3gd jHjJ GUMGH GdSbGjI Ch ZjQge HecI djGdi efi (B) s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDda (B: (3HGdLGeY GdGehi HOeTbs
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(705) s
Keywords: (3GdMOjK h GdeUWdMs